Modelling control systems using IEC 61499 - Zoitl, Alois (IET control engineering series, 2014)
This significantly updated second edition provides a thorough yet concise introduction to the main concepts and models defined in the IEC 61499 standard for modeling distributed control systems for use in factory automation.